Topics in asymmetric exchange rate pass-through to prices, digitalization, and environmental sustainability - Aiyash, Eiman (Kansas State University, 2023)
This thesis consists of three empirical chapters. Within the chapters, two investigating topics in international trade and finance using the state of the art time series Autoregressive Distributed Lag (ARDL) and Nonlinear Autoregressive Distributed Lag (NARDL) models, and the third investigating digitalization and environmental issues using panel data and Mediation Analysis. The first chapter, "Asymmetries in Exchange Rate Pass-Through to Consumer Prices." We investigate whether there are asymmetric exchange rate pass-through (ERPTH) effects on consumer prices in both the short-run and long-run, which depend on whether there is a currency appreciation or depreciation. State of the art Autoregressive Distributed Lag (ARDL) and Nonlinear Autoregressive Distributed Lag (NARDL) models are used, which have a switching structure connected to whether the exchange rate is increasing or decreasing. These questions are investigated using data from Brazil and Mexico, two top emerging countries. We find short-run asymmetric responses to exchange rate changes for Brazil, with ERPTH estimates that are positive, significant, and incomplete. However, Brazil has no long-term asymmetries, and ERPTH is negative, significant, and incomplete. On the other hand, no short-run asymmetries for Mexico are found, with ERPTH estimates that are negative, significant, and incomplete. In addition, there is a long-run asymmetry for Mexico, with an ERPTH estimate that is negative, significant, and incomplete. The second chapter, "Asymmetries in Exchange Rate Pass-Through to Trade Prices," undertakes a similar investigation as the first chapter, only here the question is whether trade (export and import) prices experience different levels of pass-through in the short-run and long-run, which depend on whether the currency is appreciating or depreciating. Again, the investigation focuses on data from Brazil and Mexico and makes use of ARDL and switching NARDL models. Starting with export prices, no evidence that there are asymmetries for Brazil in either the short-run or long-run is found, and the ERPTH estimates are negative and significant. For Mexico, only long-run asymmetry with ERPTH estimates are found to be negative, significant, and incomplete. Next, for import prices, there are consistencies between the two countries, finding short-run asymmetries and no long-run asymmetries for both countries. The short-run ERPTH estimates for Brazil are negative, significant, and more than complete. However, for Mexico, only the ERPTH estimate associated with local currency depreciation is significant, positive and incomplete. The third chapter, "Digitalization and Environmental Sustainability: Effects and Transmission Channels," examines whether the movement toward a more digital economy has helped lower the emission of carbon dioxide (CO₂) using a panel data set for the G20 countries over 30 years. Digitalization is measured with several measures for the connection between the various countries’ populations and the outside world, including mobile phone usage, fixed telephone usage, and internet usage. One of the main concerns here is to break down the connection between digitalization and carbon dioxide into direct and indirect effects, where the indirect effects operate through other channels, including trade, electricity production, fossil and fuel energy consumption, industry, and renewable energy consumption. Mediation Analysis is used to disentangle the direct and indirect effects. The findings show that internet users indirectly negatively impact the environment (increased CO₂ emissions) through its impact on trade channels and adverse effects (decreased CO₂ emissions) through fossil and fuel energy consumption, industry, and renewable energy consumption channels. Fixed telephone subscriptions have indirectly increased CO₂ emissions through their effect on all channels except the trade channel. Fixed telephone subscriptions have no indirect impact on CO₂ emissions through the trade channel. Finally, mobile cellular subscriptions have indirectly increased CO₂ emissions through trade, fossil and fuel energy consumption, and renewable energy consumption and decreased CO₂ emissions through their effect on the industry channel. Moreover, the total effects of fixed telephone usage negatively impact the environment (increased CO₂ emissions) through all channels, while the total impacts of internet users positively impact the environment (decreased CO₂ emissions) through all channels. Finally, the full effects of mobile cellular subscriptions are positive (reduced CO₂ emissions) through all channels except trade channels, where mobile cellular subscriptions increase CO₂ emissions through them.
Keywords: Exchange rate pass-through (ERPTH); Symmetric and asymmetric ERPTH; ARDL and NARDL models; Information communication technology (ICT); CO₂ emissions; Mediation analysis